The geology and geochemistry of the Sakatti Cu-Ni-PGE deposit, N. Finland - Brownscombe, William (Earth Science & Engineering, Imperial College London, 2017)
The Sakatti Cu-Ni-PGE (platinum group elements) deposit is a newly discovered mineral deposit in northern Finland. The deposit is a magmatic sulphide hosted in an ultramafic intrusion in the Central Lapland Greenstone Belt. The major lithologies and styles of mineralisation of the deposit are characterised and defined in this project and their origin investigated. The host rock is composed primarily of olivine with forsterite content between 0.85 and 0.91 and a Ni content between 3000-3700 ppm. This suggests that the olivine is undepleted with respect to Ni and has not been derived from a sulphide-saturated melt. The intrusion sits in a plagioclase-picrite and the locus of the deposit occurs at a change in gradient that occurs when the intrusion transgresses to a stratigraphically higher lithology. Sulphur isotope analysis shows that the Sakatti deposit has consistent δ34S values 2.6 ± 2.4 ‰. This is not consistent with the regional Matarakoski schists contributing S to the deposit.The deposit has unusually low Ni/Cu values, particularly the shallower portions. Magnetite trace element analysis, PPGE/IPGE values and Ni isotope analysis presented suggest that this is due to sulphide fractionation and loss of early fractionating Ni-rich sulphide cumulates. The PGE mineralogy in the Sakatti deposit is exclusively PGE tellurides, derived from sulphide melt. The dominance of tellurides leads to a wide array of moncheite-merenskyite-melonite compositions that is not seen elsewhere globally. A model is presented for the formation of the deposit where earlier Ni-rich cumulates are lost at an earlier stage in the conduit-like intrusion and remobilised by later silicate melt that does not re-equilibrate with the sulphides. Open Access